2019
DOI: 10.7554/elife.47644
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Helicobacter pylori Cag type IV secretion system

Abstract: Bacterial type IV secretion systems (T4SSs) are molecular machines that can mediate interbacterial DNA transfer through conjugation and delivery of effector molecules into host cells. The Helicobacter pylori Cag T4SS translocates CagA, a bacterial oncoprotein, into gastric cells, contributing to gastric cancer pathogenesis. We report the structure of a membrane-spanning Cag T4SS assembly, which we describe as three sub-assemblies: a 14-fold symmetric outer membrane core complex (OMCC), 17-fold symmetric peripl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
166
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(170 citation statements)
references
References 29 publications
(75 reference statements)
4
166
0
Order By: Relevance
“…CagY (residues 1677-1909) are localized to central regions of the O-layer of the OMC (Chung et al, 2019). The increased resolution of the new maps allowed us to define the OMC asymmetric unit and determine the molecular composition of regions that were previously undefined ( .…”
Section: Resultsmentioning
confidence: 99%
“…CagY (residues 1677-1909) are localized to central regions of the O-layer of the OMC (Chung et al, 2019). The increased resolution of the new maps allowed us to define the OMC asymmetric unit and determine the molecular composition of regions that were previously undefined ( .…”
Section: Resultsmentioning
confidence: 99%
“…Structural details for several IVA machines have furthered our understanding of how these systems function. Xanthomonas citri VirB/D-, Helicobacter pylori Cag-, and E. coli R388-encoded IVA secretion machine structures resolved by single-particle cryoelectron microscopy (cryo-EM) and X-ray crystallography revealed that the IVA secretion machines are composed of an outer membrane-associated core complex (OMCC) that includes a large periplasmic assembly of proteins that connects to the secretion channel in the outer membrane (9)(10)(11)(12)(13). The OMCC recruits integral inner membrane (IM) proteins that connect to a cytoplasmic complex.…”
mentioning
confidence: 99%
“…The apparent stoichiometric mismatches among subcomplexes could be in fact an important flexibility factor key to T4SS function. In this respect, it is interesting to note that the recently reported near‐atomic resolution structure of the Cag T4SS (Chung et al, ) shows that the 14‐fold symmetric outer membrane core complex connects to a newly described 17‐fold symmetric periplasmic ring complex. This new structure illustrates the structural diversity among T4SS.…”
Section: Structure and Function Of T3 T4 And T6ssmentioning
confidence: 96%